GEOPHYSICAL EVALUATION OF ROCK TYPES IMPART ON THE AQUIFER SYSTEMS IN THE BASEMENT COMPLEX TERRAIN, SOUTHWESTERN NIGERIA (FULafia Journal of Science and Technology, 2020)
A study was carried out to determine the Landsat ETM+, aeromagnetic and vertical electrical sounding (VES) data covering Ado-Ekiti with the intent of delineating the lithological contact, basement structures and aquifer systems in the area. The Landsat imagery generated was processed using PCI Geomatica software, aeromagnetic data procured was processed using Oasis MontajTM and VES data was processed with partial curve matching technique assisted with 1-D forward modelling. The lineaments density (Ld) from the analysis of Landsat ETM+ ranges between low to high. Ld is higher over and around lithological contacts and areas underlainby felsic rocks. Interpretation of aeromagnetic data allows identification of series of anomalies suspected to be lithological contacts through the application of analytic signal, tilt derivative and Euler deconvolution. Qualitatively analysis of the two hundred and sixteen (216) sounding curves showed that the study area was predominated by A, H, KH, HK, QH and HKH –type curves